IMMUNOLOGICAL CHANGES AS A RESULT OF HEAD INJURY, THAT LEAD TO DEPRESSION - Bedlinskyi, V.O. (The Ukrainian Scientific Medical Youth Journal, 2018)
Relevance. Depression is the one of the most frequent psychiatric conditions, that is developed as a result of head injury. The frequency of post-traumatic depression accounts from 6% to 77%. The etiology is still unknown, although one of the main etiopathogenic link are changes in the immunological reactivity. Aim. Analysis of the main mechanisms of the influence of immune system, triggered by head injury, on development of depression symptoms. Methods. Data from Web of Science, Pubmed and Google Scholar were analyzed with key words: depression, organic depressive disorder, head injury, immune response. Results. Current methods in the treatment of the organic depression can’t fully influence on main pathogenic link. It can complicate the treatment and lead to exacerbation or delayed outcomes of the head injury.